2023
DOI: 10.31234/osf.io/p4gza
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

German mHealth App Usability Questionnaire (G-MAUQ): Translation and Validation Study

Abstract: Background: The use of mobile health applications is increasingly common among the general public. More recently, healthcare systems incorporate such tools in their service workflows, be it as guidance to the most appropriate care setting or as prescription digital therapeutics. With such apps percolating into the classic healthcare sector, the necessity of sound and standardized evaluation grows. The mHealth App Usability Questionnaire (MAUQ) provides a novel and custom-tailored psychometrically validated ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…For the brief version, reliability was still acceptable with Cronbach ś alpha of 0.72. Different authors in this field offered German translations of the mHealth App Usability Questionnaire (MAUQ) (25,26,27). Moorthy et al validated their translated MAUQ in a specific sample of 133 cancer patients but (presumably due to the small sample size) the factor structure of the translated questionnaire was not further investigated (25).…”
Section: Usability Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the brief version, reliability was still acceptable with Cronbach ś alpha of 0.72. Different authors in this field offered German translations of the mHealth App Usability Questionnaire (MAUQ) (25,26,27). Moorthy et al validated their translated MAUQ in a specific sample of 133 cancer patients but (presumably due to the small sample size) the factor structure of the translated questionnaire was not further investigated (25).…”
Section: Usability Questionnairesmentioning
confidence: 99%
“…Moorthy et al validated their translated MAUQ in a specific sample of 133 cancer patients but (presumably due to the small sample size) the factor structure of the translated questionnaire was not further investigated (25). Kopka et al provided a German version and a German short version in a sample of 148 patients using a symptom checker app in an emergency department in a randomized controlled trial (26). They showed that the original factor structure did not fit the data well, but no further investigation of the factor structure was conducted.…”
Section: Usability Questionnairesmentioning
confidence: 99%